IFPRI-CCAFS Gender and Climate Change Survey Data: Bangladesh - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
The IFPRI-CCAFS Gender and Climate Change Survey data were collected between April and May 2013 as part of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) under the project "Increasing Women’s Resilience to Confront Climate Change." It aimed to enhance understanding of gendered climate change perceptions, impacts, adaptation, and coping strategies, as well as the constraints to adaptation within two CCAFS research sites in Bangladesh, Bagerhat and Satkhira. Data were collected on the three previous agricultural seasons, that is, from August 2011 to August 2012. The survey covered the same households that were sampled for the IMPACT Lite surveys, designed by researchers at the International Livestock Research Institute (ILRI) in order to supplement the detailed productivity-related information collected through that survey. Gender-disaggregated data were gathered on climate change perceptions, agricultural activities, decision-making, weather information, risk perceptions, and adaptation. Information was also collected on assets, farming decisions, agricultural practices, respondents’ access to information, extension services, and credit; and their participation in community groups. Data were gathered through the use of questionnaires administered through face-to-face interviews. Two adult decision makers (one male and one female) were interviewed separately per household in order to capture independent perceptions.